2020
DOI: 10.1177/1759720x20953336
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of sirolimus in systemic lupus erythematosus: a real-world study and meta-analysis

Abstract: Objective: To provide real-world data and summarize current clinical evidence on the efficacy and safety of sirolimus in active systemic lupus erythematosus (SLE) patients. Methods: This was a prospective real-world clinical study. Included SLE patients should have Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) ⩾ 2. They were treated with sirolimus and followed up regularly. The SLEDAI-2K, Physician Global Assessment (PGA), serological activity indices, and remission of organ manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Increasing evidence regarding the use of the mTOR inhibitor rapamycin (also called sirolimus) as a new potential treatment regimen for LN has been gained from animal models since 2008 3 , 4 and patient trials since 2009. 5 9 A single-arm, open-label, phase 1/2 trial and a real-world study confirmed the safety and efficacy of oral sirolimus in the treatment of SLE. 10 , 11 Retrospective studies reported LN patients who responded to sirolimus as an induction or maintenance therapy.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Increasing evidence regarding the use of the mTOR inhibitor rapamycin (also called sirolimus) as a new potential treatment regimen for LN has been gained from animal models since 2008 3 , 4 and patient trials since 2009. 5 9 A single-arm, open-label, phase 1/2 trial and a real-world study confirmed the safety and efficacy of oral sirolimus in the treatment of SLE. 10 , 11 Retrospective studies reported LN patients who responded to sirolimus as an induction or maintenance therapy.…”
Section: Introductionmentioning
confidence: 79%
“…Among 17 active LN patients who were treated with sirolimus, 7 had a renal response by 3 to 9 months, whereas another 10 patients experienced worsening of proteinuria. 9 The discrepancy in the treatment response might be explained by the different inclusion criteria. PUMCH enrolled refractory patients with either intolerance or a poor response to the previous immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Its effectiveness and safety in SLE treatment have been reported in uncontrolled studies. [13][14][15][16] However, a comparison of sirolimus with other classic immunosuppressants has not been reported. In our study, tacrolimus was chosen as the positive control due to its structural similarities with sirolimus and its proven effectiveness as a medication recommended for SLE treatment according to several guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that it has both mechanical and clinical therapeutic effects on SLE. [10][11][12][13][14][15][16] However, as a newly used medicine for SLE, more evidence and comparisons with other immunosuppressants are necessary to prove its efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…The activated mTOR pathway has been detected in LN and has emerged as a central pathway for pathogenesis and treatment with rapamycin or other mTOR inhibitors, displaying protective and beneficial effects for LN [ 15 , 16 ]. In our previous study, ADSC (passage 4) transplantation prevented LN development and ameliorated already-established disease via the mTOR/HIF-1 α signal pathway [ 10 ].…”
Section: Introductionmentioning
confidence: 99%